Clinical and Histopathological Relevance of Helicobacter pylori BabA2 Genotype - Elhashim, Tariq; Mahmud, M. Imad Mustafa; Amjad, Nasser; Harun, Norra; Alani, Imad M. (IIUM Medical Journal Malaysia, 2016)
Introduction: H. pylori BabA is an outer membrane protein that mediates bacterial adherence to the gastric epithelium, triggers several pathways during the course of infection, and thus contributes to the disease development. Considering the variability in the presence of BabA coding gene (babA2) among H. pylori clinical strains, the aim of this study was to assess the relationship between the genotype status of H. pylori babA2 and the severity of clinical and histopathological outcomes. Methods: Gastric mucosal biopsy specimens were collected from 30 CLO test-positive patients, 16 with gastritis and 14 with peptic ulcer disease. Polymerase chain reaction was carried out to detect the presence of H. pylori-specific glmM gene and BabA coding gene (babA2). Histopathological examination was performed to evaluate the severity of H. pylori-associated gastric disease according to the Updated Sydney Classification System. Results: The glmM and babA2 genes were present in 100% and 86.7% of the tested H. pylori strains, respectively. Although higher degrees of inflammatory activity and H. pylori density were noted in babA2-positive biopsy specimens, there was no statistically significant association between babA2 genotype status and the severity of gastric disease. Conclusion: The babA2 genotype status of H. pylori may not be considered as a sole marker for determining the infection outcomes.